A judicial misconception of mosque disputes in common law jurisdiction: The supreme court's declaration of high court's jurisdiction in imamship disputes in Nigeria - Syed Abdul Kader, Sharifah Zubaidah; Ishola, Abdullahi Saliu (Miyetti Research and Publications, 2017)
This paper reveals the Supreme Court's declaration of jurisdiction in Imamship disputes in Nigeria as being vested in the High Court, as done in the case of Abdulsalam v Salawu, as a demonstration of judicial misconception of mosque disputes in Islamic personal law matters vests in the Sharia Court of Appeal and its correspondent lower court respectively and with waqf being an Islamic personal law matter, it is not yet understood that Mosque is Waqf in Islamic law and mosque disputes are a conflict over waqf management. Accordingly, adopting the doctrinal legal research methodology and the context analysis technique, this paper undergoes a critique of the case of Abdulsalam and explains why the Supreme Court got it wrong in its decision. Even though the case should have a binding force on all other courts till reviewed by the Supreme Court, the legal technique by which the case can be jettisoned ids clarified for use pending such reviews.